PENDIDIKAN PANCASILA, EKSISTENSINYA BAGI MAHASISWA - August Hadiwijono (Jurnal Cakrawala Hukum, 2016)
This study attempts to analyze the meaning of Pancasila for students and went to analyze Pancasila’s way oncampus. The research is normative research. Development and education of Pancasila need to be done by a collegein order to preserve Pancasila values and planting positive values, contained in it for the young generationespecially students the student who have important and vital. In addition to Pancasila as an ideology andpersonality of the country. Pancasila as a view of life nations must be from early introduced and taught tocommunities Indonesia including college. As forming the intellectual ethical lordship and humanity. The Pancasilapersonality must be personality the youth particularly university students who became generation education.Through education of Pancasila, students will be human first, before entering the lecture which learned. As acitizen of Indonesia who excels in knowledge mastery, but not lost their identity and not drawn from the rootculture her people and his faith. In addition, it can form personally good in social norms and had good in order tobecome very good citizens for themselves, others and this person in daily life. I have values Pancasila in students wecan do it in on several, that is an education channel and the organization and message objectively and subjectively. If the values of Pancasila embedded with both in each individual student will be created Pancasila studentwho understands norms. Pancasila implementation in life on campus was very important it is for the sake ofadvance college to campus can produce graduates Pancasila students cannot be built by the people of Indonesia.